Visual computing for medicine theory, algorithms, and applications - Preim, Bernhard; Botha, Charl (The Morgan Kaufmann series in computer graphics, 2014)
This book offers cutting-edge visualization techniques and their applications in medical diagnosis, education, and treatment. It includes algorithms, applications, and ideas on achieving reliability of results and clinical evaluation of the techniques covered, and treatment planning, guidance, and training.